The relationship between body composition and clinical parameters in chronic obstructive pulmonary disease - Chaicharn Pothirat (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: Identify a correlation between body mass index (BMI) and fat-free mass index (FFMI) to clinical parameters in chronic obstructive pulmonary disease. Material and Method: The cross-sectional study was conducted at a single visit involving stable chronic obstructive pulmonary disease (COPD) patients at the outpatient chest clinic of the Chiang Mai University Hospital, Thailand. Eligible patients were evaluated for BMI, FFMI, lung function, modified medical research council (mMRC) dyspnea score, COPD assessment test (CAT) score, and number of acute exacerbation (AE) in the past year. The correlations of FFMI and BMI with other parameters were determined using Pearson correlation coefficient analysis. Body composition was categorized into four groups, normal, semi-starvation, muscle atrophy/sarcopenia, and cachexia based on BMI and FFMI. Statistical significance was accepted at p-value <0.05. Results: One hundred twenty one stable COPD patients met study inclusion criteria. The FFMI showed a strong correlation with BMI (r = 0.792, p<0.001). The FFMI, but not BMI, was significantly correlated with mMRC, precentage of predicted forced expiratory volume in first second (FEV1), and CAT score (r = -0.315, 0.214, and -0.278, respectively). Body composition was categorized into four groups: normal body composition (n = 62, 51.2%), semi-starvation (n = 4, 3.3%), sarcopenia muscular atrophy (n = 12, 9.9%), and cachexia (n = 43, 35.5%). Conclusion: FFMI, but not BMI, was significantly correlated with dyspnea severity, lung function, and quality of life. Body composition category assignment is a useful clinical tool.